Relationship between parent’s religious orientation, verbal communication and sociability of primary school students (second course) in Zahedan city - JAMALZEHI MOGHADDAM, M.; BALAGHAT, S.R. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study aimed to evaluate the relationship between parents’ religious orientation with communication and socialization of students. The research method was descriptive in a correlational way. The statistical community included all male and female students of the elementary school of Zahedan city in the school year 94-95 that 383 people selected as a sample with the Cochran sampling method. Results showed that parents has more internal and verbal communication and students listens to a religious orientation that between the religious orientation of parents accomplish a verbal communication and socialization RESUMEN El objetivo de este estudio fue evaluar la relación entre la orientación religiosa de los padres con la comunicación y la socialización de los estudiantes. La comunidad estadística incluyó a estudiantes masculinos y femeninos de la escuela primaria del Distrito 1 de la ciudad de Zahedan en el año educativo 94-95 que 383 personas seleccionaron como muestra con el método de muestreo Cochran. Los resultados mostraron que los padres tienen más comunicación interna y verbal y que los estudiantes escuchan más la orientación religiosa y la orientación religiosa de los padres con la socialización poseen una relación significativa.